Analisis Faktor Profesional Teungku Dayah Istiqamatuddin Serambi Aceh Kabupaten Bireuen - Munajar, Teungku; Kamaruddin, Kamaruddin; Sylvia, Rizka (peusangan, 2025)
Currently, the demands on dayah education continue to need to be improved, starting with the professionalism of Teungku, namely the teachers at the dayah. Many factors make someone professional, including the results of their education, competence and experience. This study tries to analyze the professionalism of teungku from these factors at Dayah Istiqamatuddin Serambi Aceh in Bireuen Regency. The study uses an associative approach with a quantitative approach. Based on the statistical inference analysis model with path analysis, the results show that; 1) there is a causal relationship between education, competence and experience factors. 2) there is a direct and indirect influence of education level on teungku professionalism of 44.98%. 3) there is a direct and indirect influence of competence on teungku professionalism of 39.37%. 4) there is a direct and indirect influence of teaching experience on teungku professionalism of 48.1%. 5) Simultaneously, education level, competence and teaching experience influence Teungku professionalism by 71.0%.